"المعالجة المحاسبية للأجور والرواتب والتصريحات الجبائية والشبه الجبائية لهما دراسة ميدانية - " - سناء, زغدي; عبد الرؤوف, سعد العايب; عبير, قدادرة (University of eloued جامعة الوادي, 2020)
"تهدف الدراسة لإبراز العناصر المكونة للراتب والمعايير المعتمدة في حسابه، مع المعالجة المحاسبة له، وقد أخذت هذه الدراسة شرح وعرض لمكونات الراتب من منح وتعويضات ومكافآت بالإضافة إلى الإقتطاعات والمعالجة المحاسبية التي تطبق عليه. وللإجابة على إشكالية البحث فقد تم الإعتماد على المنهج الوصفي التحليلي عن طريق ما توفر من معلومات حول متغيرات الدراسة من كتب، مجلات، مذكرات ونصوص قانونية وتنظيمية. ولدعم الجانب النظري فلقد إعتمدنا في الجانب التطبيقي على الدراسة الميدانية في كل من مصلحة تسيير نفقات المستخدمين بمديرية التربية لولاية الوادي، مؤسسة خاصة (شركة الضيف للخدمات) ومؤسسة اقتصادية الصندوق الوطني للضمان الاجتماعي لغير الأجراء (CASNOS). ومن خلال دراستنا للأجور ومحاسبتها أن الأجر له عدة مكونات من أجر أساسيـ تعويضات، مجموعة من المكافآت والإقتطاعات والتي تنظمها نصوص قانونية وتنظيمية. ولذا فمحاسبة الأجور هي عملية معقدة نوعا ما كونها تخضع لعدة قوانين وهي: قانون العمل – التشريع الجبائي – الضمان الإجتماعي ""The study aims to highlight the components of the salary and the standards adopted in his account, with the accounting treatment of it, and this study took an explanation and presentation of the salary components of grants, compensations and bonuses in addition to deductions and the accounting treatment applied to it. In order to answer the research problem, the descriptive and analytical approach was relied upon through the available information about the study variables in books, magazines, notes, and legal and organizational texts. In order to support the theoretical side, we have relied, on the practical side, on the field study in each of the administration of employee expenses in the Directorate of Education of the State of El-oeud, a private institution (the Guest Services Company) and an economic institution, the National Social Security Fund for Non-Wages (CASNOS). Through our study of wages and their accounting, the wage has several components of a basic wage, compensation, a set of rewards and deductions that are regulated by legal and regulatory texts. -Therefore, accounting wages is a rather complicated process, as it is subject to several laws, namely: labor law - tax legislation - social security. "
مذكرة ماستر محاسبة
Keywords: الأجور والرواتب – الضرائب الجبائية والشبه جبائية – المعالجة المحاسبية; wages and salaries - tax and quasi-tax taxes - accounting treatment